Complete genome sequence of the thermophilic sulfur-reducer Desulfurobacterium thermolithotrophum type strain (BSAT) from a deep-sea hydrothermal vent - Göker, M.; Daligault, H.; Mwirichia, Romano K.; Lapidus, A.; Lucas, S.; Deshpande, S.; et al. (My University, 2011)
Desulfurobacterium thermolithotrophum L'Haridon et al. 1998 is the type species of the ge-nus Desulfurobacterium which belongs to the family Desulfurobacteriaceae. The species is of interest because it represents the first thermophilic bacterium that can act as a primary pro-ducer in the temperature range of 45-75 °C (optimum 70°C) and is incapable of growing un-der microaerophilic conditions. Strain BSAT preferentially synthesizes high-melting-point fatty acids (C18 and C20) which is hypothesized to be a strategy to ensure the functionality of the membrane at high growth temperatures. This is the second completed genome sequence of a member of the family Desulfurobacteriaceae and the first sequence from the genus Desulfu-robacterium. The 1,541,968 bp long genome harbors 1,543 protein-coding and 51 RNA genes and is a part of the Genomic Encyclopedia of Bacteria and Archaea project.
DOI:10.4056/sigs.2465574
Keywords: anaerobic; thermophilic; neutrophilic; obligately chemolithoautotrophic; Gram-negative; marine; sulfur-reducing; Desulfurobacteriaceae; GEBA